Failure of early non-invasive ventilation in preterm infants with respiratory distress syndrome in current care practice in Spanish level-III neonatal intensive care units – a prospective observational study - Boix, Hector; Fernández, Cristina; Serrano Martín, María del Mar; Arruza, Luis; Concheiro, Ana; Gimeno, Ana; Sánchez, Ana; Rite, Segundo; Jiménez, Francisco; Méndez, Paula; Agüera, Juan José; , on behalf of the VENTIS study research group (Frontiers in Pediatrics, 2023)
Introduction: Despite advances in respiratory distress syndrome (RDS) management over the past decade, non-invasive ventilation (NIV) failure is frequent and associated with adverse outcomes. There are insufficient data on the failure of different NIV strategies currently used in clinical practice in preterm infants. Methods: This was a prospective, multicenter, observational study of very preterm infants (gestational age [GA] <32 weeks) admitted to the neonatal intensive care unit for RDS that required NIV from the first 30 min after birth. The primary outcome was the incidence of NIV failure, defined as the need for mechanical ventilation for <72 h of life. Secondary outcomes were risk factors associated with NIV failure and complication rates. Results: The study included 173 preterm infants with a median GA of 28 (IQR 27-30) weeks and a median birth weight of 1100 (IQR 800-1333) g. The incidence of NIV failure was 15.6%. In the multivariate analysis, lower GA (OR, 0.728; 95% CI, 0.576-0.920) independently increased the risk of NIV failure. Compared to NIV success, NIV failure was associated with higher rates of unfavorable outcomes, including pneumothorax, intraventricular hemorrhage, periventricular leukomalacia, pulmonary hemorrhage, and a combined outcome of moderate-to-severe bronchopulmonary dysplasia or death. Conclusion: NIV failure occurred in 15.6% of the preterm neonates and was associated with adverse outcomes. The use of LISA and newer NIV modalities most likely accounts for the reduced failure rate. Gestational age remains the best predictor of NIV failure and is more reliable than the fraction of inspired oxygen during the first hour of life.